A coating agent coated pre-sodiumized hard carbon and pre-sodiumized hard carbon dry-process electrode and preparation method thereof
Through the pre-sodium hardened carbon preparation method coated with a coating agent, the problem of low storage capacity and irreversible consumption of hard carbon electrodes in sodium ion batteries is solved, and the effect of improving the energy density and circulation performance of sodium ion batteries is achieved.
Patent Information
- Application Number
- CN202311462813.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-11-03
AI Technical Summary
The negative electrode material of existing sodium ion batteries has a low storage capacity of hard carbon. The formation of solid electrolyte membrane on the surface during the first charging and discharging process leads to irreversible consumption, which reduces energy density and cycling performance.
The pre-sodium hardened carbon preparation method coated with a coating agent is used to carbonize biomass and waste plastic powder, and then coat with dimethyl terephthalate to form a stable SEI film.
It improves the first charge and discharge efficiency, cycle performance, rate performance and energy density of sodium ion batteries, and enhances the reversibility and safety of hard carbon electrodes.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hard carbon materials, and in particular to a pre-sodiumized hard carbon coated with a coating agent and a pre-sodiumized hard carbon dry-process pole piece and a preparation method thereof. Background Art
[0002] Sodium-ion batteries are expected to become a substitute for lithium-ion batteries due to their outstanding advantages such as abundant resources, low price and wide distribution, especially in future large-scale energy storage systems. The energy density of sodium ions is lower than that of lithium iron phosphate batteries and ternary batteries, and the lower energy density limits their commercial application.
[0003] Hard carbon has been widely studied due to its low cost, high specific capacity and appropriate redox potential for sodium. It is composed of curved, randomly oriented and defective carbon layers with carbon rings and surface oxygen-containing functional groups such as hydroxyl and carboxyl groups. Hard carbon belongs to carbon that is difficult to graphitize. Its characteristics are that the layered molecules have few parallel structures and the arrangement of carbon atoms is mostly curved and folded, so it is easy to form micropores. This structure is particularly suitable for the insertion and deinsertion of sodium ions. At present, the negative electrode materials suitable for commercial sodium-ion batteries are all hard carbon. However, hard carbon has low storage capacity, and the solid electrolyte film formed on the surface of hard carbon during the first charge and discharge process causes irreversible consumption, resulting in low first coulombic efficiency, which reduces the energy density of sodium-ion batteries with hard carbon-based negative electrodes. It is necessary to improve the energy density and cycle performance of sodium-ion batteries through pre-sodium treatment. Na absorption in graphite domains and the pores constructed by them contribute to the reversibility of hard carbon electrodes. However, the sodiation of carbon defects and oxygen-containing functional groups is irreversible and also affects the formation of SEI, which leads to low CE, cyclic degradation and safety issues of hard carbon electrodes.
[0004] Therefore, it is of great significance to study and obtain a pre-sodiumized hard carbon that can improve the charge and discharge efficiency and specific capacity of sodium-ion batteries and have good cycle stability. Summary of the invention
[0005] The purpose of the present invention is to provide a coating agent-coated pre-sodiumized hard carbon and a pre-sodiumized hard carbon dry-process electrode and a preparation method thereof in view of the deficiencies in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing pre-sodiumized hard carbon coated with a coating agent, comprising the following steps:
[0008] 1) Pre-carbonizing the phosphorylated biomass and waste plastic powder to obtain a hard carbon precursor;
[0009] 2) carbonizing the hard carbon precursor, waste plastic powder and nano oxide to obtain hard carbon powder;
[0010] 3) subjecting hard carbon powder and metallic sodium powder to a pre-sodiumization reaction under an inert gas to obtain pre-sodiumized hard carbon;
[0011] 4) The pre-sodium-treated hard carbon and the coating agent are mixed and reacted to obtain the pre-sodium-treated hard carbon coated with the coating agent.
[0012] Preferably, in step 1), the mass ratio of the phosphorylated biomass to the waste plastic powder is 3:1-2; the phosphorylated biomass is obtained by mixing the biomass powder and phosphoric acid in a mass ratio of 10:0.5-1; the biomass powder comprises one or more of bagasse, bamboo powder and reed powder.
[0013] Preferably, the waste plastic powder in step 1) and step 2) comprises one or more of waste polyethylene terephthalate, waste phenolic resin and waste polycarbonate; and the nano-oxide in step 2) comprises one or more of nano-aluminum oxide, nano-silicon oxide, nano-titanium oxide, nano-magnesium oxide, nano-tin oxide and nano-silicon oxide.
[0014] Preferably, the temperature of the pre-carbonization reaction in step 1) is 200-600° C., and the time of the pre-carbonization reaction is 2-5 hours;
[0015] Step 2) The carbonization temperature is 1300-1500° C., the carbonization time is 1-3 hours, and the rate of heating to the carbonization temperature is 2-7° C. / min.
[0016] Preferably, in step 2), the mass ratio of the hard carbon precursor, waste plastic powder and nano-oxide is 4:2-3:1-2; and in step 3), the mass ratio of the hard carbon powder and metallic sodium powder is 10:1-3.
[0017] Preferably, the temperature of the pre-sodiumization reaction in step 3) is 180-220° C., and the time of the pre-sodiumization reaction is 0.5-1.5 h; the metallic sodium powder is metallic sodium powder crushed in liquid nitrogen; the inert gas is nitrogen or argon, and the flow rate of the inert gas is 2-8 L / min.
[0018] Preferably, in step 4), the coating agent is dimethyl terephthalate, and the mass ratio of pre-sodium hard carbon to dimethyl terephthalate is 1:2-4; the mixing temperature is 55-65°C, the reaction temperature is 160-180°C, and the reaction time is 0.5-2h.
[0019] The present invention also provides pre-sodiumized hard carbon coated with a coating agent prepared by the preparation method.
[0020] The present invention also provides a method for preparing a pre-sodiumized hard carbon dry-process electrode from the pre-sodiumized hard carbon coated with the coating agent, comprising the following steps:
[0021] The pre-sodiumized hard carbon coated with a coating agent, a binder and conductive carbon black are mixed, and the mixture is hot-pressed and coated on a carbon-coated aluminum foil to obtain a pre-sodiumized hard carbon dry-process electrode;
[0022] The thickness of the carbon-coated aluminum foil is 25 to 35 μm, and the coating thickness of the mixture on the carbon-coated aluminum foil is 60 to 75 μm;
[0023] The mass ratio of the pre-sodiumized hard carbon coated by the coating agent, the binder and the conductive carbon black is 20:1-3:1-2; the binder is polyvinylidene fluoride and / or polyethylene terephthalate.
[0024] The present invention also provides a pre-sodiumized hard carbon dry-process electrode prepared by the preparation method.
[0025] The beneficial effects of the present invention include:
[0026] 1) During the high-temperature carbonization process of the present invention, molten Na directly reacts with the hydroxyl and carboxyl groups on the surface of the hard carbon, sodium transfers electrons to the layered hard carbon material, and sodium ions migrate into the layered structure of the hard carbon. The subsequent electrophilic properties of the electron-rich layered structure cause a portion of the metallic sodium to continue to accumulate in the pores of the layered structure. Excess dimethyl terephthalate is added to the pre-sodium hard carbon, and the molten dimethyl terephthalate reacts with the excess sodium in the excess sodium-pre-sodium hard carbon mixture to generate sodium terephthalate. At the same time, a slightly excess amount of dimethyl terephthalate is coated on the surface of the pre-sodium hard carbon to isolate the air and improve the air stability of the pre-sodium hard carbon product.
[0027] 2) After the pre-sodiumized hard carbon coated with dimethyl terephthalate is made into a pole piece, dimethyl terephthalate is dissolved in an electrolyte or coupled with a solid electrolyte membrane, exposing the active surface of the hard carbon, and the residual sodium terephthalate salt participates in the formation of an SEI film as a solid electrolyte, thereby increasing the transmission rate of sodium ions on the hard carbon surface and reducing the interface impedance. The pre-sodiumized hard carbon of the present invention can be used as a negative electrode material for a sodium ion battery to simultaneously improve the initial charge and discharge efficiency, cycle performance, rate performance, and energy density of the sodium ion battery. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing pre-sodiumized hard carbon coated with a coating agent, comprising the following steps:
[0029] 1) Pre-carbonizing the phosphorylated biomass and waste plastic powder to obtain a hard carbon precursor;
[0030] 2) carbonizing the hard carbon precursor, waste plastic powder and nano oxide to obtain hard carbon powder;
[0031] 3) subjecting hard carbon powder and metallic sodium powder to a pre-sodiumization reaction under an inert gas to obtain pre-sodiumized hard carbon;
[0032] 4) The pre-sodium-treated hard carbon and the coating agent are mixed and reacted to obtain the pre-sodium-treated hard carbon coated with the coating agent.
[0033] In the present invention, the mass ratio of the phosphorylated biomass and the waste plastic powder in step 1) is preferably 3:1-2, and more preferably 3:1.5; the phosphorylated biomass is preferably obtained by mixing biomass powder and phosphoric acid in a mass ratio of 10:0.5-1, and more preferably obtained by mixing biomass powder and phosphoric acid in a mass ratio of 10:0.7-0.8; the biomass powder preferably comprises one or more of bagasse, bamboo powder and reed powder.
[0034] In the present invention, the phosphorylated biomass has a rich closed-pore structure, which can effectively improve the sodium storage capacity, electronic conductivity and energy density of the battery.
[0035] In the present invention, the waste plastic powder in step 1) and step 2) preferably comprises one or more of waste polyethylene terephthalate, waste phenolic resin and waste polycarbonate; the nano oxide in step 2) preferably comprises one or more of nano aluminum oxide, nano silicon oxide, nano titanium oxide, nano magnesium oxide, nano tin oxide and nano silicon oxide.
[0036] In the present invention, the temperature of the pre-carbonization reaction in step 1) is preferably 200-600° C., more preferably 300-530° C., and more preferably 450-480° C.; the time of the pre-carbonization reaction is preferably 2-5 hours, and more preferably 3-4 hours;
[0037] Step 2) The carbonization temperature is preferably 1300-1500°C, more preferably 1350-1450°C, and more preferably 1400°C; the carbonization time is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h; the rate of heating to the carbonization temperature is preferably 2-7°C / min, more preferably 3-6°C / min, and more preferably 4-5°C / min.
[0038] In the present invention, when the carbonization temperature is too high, the specific surface area of the hard carbon material is reduced, thereby lowering the electrical properties of the hard carbon material. When the carbonization temperature is too low, it is difficult to achieve the purpose of carbonization.
[0039] In the present invention, the mass ratio of the hard carbon precursor, waste plastic powder and nano oxide in step 2) is preferably 4:2-3:1-2, more preferably 4:2.2-2.8:1.2-1.8, and more preferably 4:2.4-2.5:1.4-1.6; and the mass ratio of the hard carbon powder and metallic sodium powder in step 3) is preferably 10:1-3, more preferably 10:1.5-2.5, and more preferably 10:2.
[0040] In the present invention, the temperature of the pre-sodiumization reaction in step 3) is preferably 180-220°C, more preferably 190-210°C, and more preferably 200°C; the time of the pre-sodiumization reaction is preferably 0.5-1.5h, and more preferably 1h; the metallic sodium powder is preferably metallic sodium powder crushed in liquid nitrogen; the inert gas is preferably nitrogen or argon, and the flow rate of the inert gas is preferably 2-8L / min, more preferably 3-7L / min, and more preferably 4-5L / min.
[0041] In the present invention, the coating agent in step 4) is preferably dimethyl terephthalate, and the mass ratio of pre-sodium hard carbon to dimethyl terephthalate is preferably 1:2-4, more preferably 1:2.5-3.5, and more preferably 1:3; the mixing temperature is preferably 55-65°C, more preferably 58-62°C, and more preferably 60°C; the reaction temperature is preferably 160-180°C, more preferably 165-175°C, and more preferably 170°C; the reaction time is preferably 0.5-2h, and more preferably 1-1.5h.
[0042] In the present invention, phosphorus element and pre-sodium treatment improve the capacity, rate performance and first coulombic efficiency of the hard carbon material, and pre-sodium treatment can increase the interlayer spacing of the hard carbon.
[0043] In the process of the pre-sodiumization reaction of the present invention, it is preferred that an inert gas is filled into the vacuum after evacuation, and then the metallic sodium powder is added; the vacuum degree is preferably 0.08-0.09 MPa, and more preferably 0.085 MPa.
[0044] In the present invention, reasonable control of the mass ratio of metallic sodium and hard carbon powder is beneficial to improving the first coulombic efficiency and rate performance of the hard carbon negative electrode. When the metallic sodium content is too high, the cycle life of the battery will be reduced. When the metallic sodium content is too low, the pre-sodiumization effect is not obvious and the first coulombic efficiency is low.
[0045] The present invention also provides pre-sodiumized hard carbon prepared by the preparation method.
[0046] The present invention also provides a method for preparing a pre-sodiumized hard carbon dry-process electrode from the pre-sodiumized hard carbon coated with the coating agent, comprising the following steps:
[0047] The pre-sodiumized hard carbon coated with a coating agent, a binder and conductive carbon black are mixed, and the mixture is hot-pressed and coated on a carbon-coated aluminum foil to obtain a pre-sodiumized hard carbon dry-process electrode;
[0048] The thickness of the carbon-coated aluminum foil is 25 to 35 μm, and the coating thickness of the mixture on the carbon-coated aluminum foil is 60 to 75 μm;
[0049] The mass ratio of the pre-sodiumized hard carbon coated by the coating agent, the binder and the conductive carbon black is 20:1-3:1-2; the binder is polyvinylidene fluoride and / or polyethylene terephthalate.
[0050] In the present invention, the mass ratio of the pre-sodiumized hard carbon coated with the coating agent, the binder and the conductive carbon black is preferably 20:1.5-2.5:1.2-1.8, and more preferably 20:1.8-2:1.4-1.5.
[0051] In the present invention, the appropriate coating amount can make the hard carbon change from open pores to closed pores, reduce the specific surface area and pore volume of the hard carbon material, and thus improve the low platform capacity. When the coating ratio is too high, it will lead to a decrease in specific capacity. At the same time, too thick a coating layer can increase the resistance of desolvated ions to diffuse into the pores and reduce the low platform capacity. When the coating ratio is too low, it will lead to a large number of open pores, resulting in excessive SEI film formation, making it difficult to achieve the purpose of closed-pore sodium storage.
[0052] In the present invention, after coating is completed, a roller machine is used for hot pressing to obtain a pre-sodiumized hard carbon dry-process electrode; the surface of the roller machine has a titanium nitride protective layer. During the hot pressing process, the gap range of the roller machine is preferably 20 to 40 μm, and more preferably 25 to 35 μm; the pressure is preferably 30 to 50 tons, and more preferably 35 to 45 tons, and the temperature is preferably 100 to 120°C, and more preferably 105 to 115°C.
[0053] The present invention also provides a pre-sodiumized hard carbon dry-process electrode prepared by the preparation method.
[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0055] Example 1
[0056] 60g of phosphorylated bagasse (phosphorylated bagasse is obtained by mixing bagasse and phosphoric acid at a mass ratio of 10:0.6 for 2 hours, and the mass concentration of phosphoric acid is 55%) and 24g of waste bisphenol A polycarbonate powder are mixed and crushed into blocks, pre-carbonized at 300°C for 5 hours, and the pre-carbonized product is crushed to obtain a hard carbon precursor. 40g of hard carbon precursor, 22g of waste bisphenol A polycarbonate powder and 12g of nano magnesium oxide are mixed, heated to 1350°C at a rate of 3°C / min, carbonized at 1350°C for 3 hours, and then crushed to obtain hard carbon powder.
[0057] Put 30g of hard carbon powder into a vacuum vibration dryer (power is 5kW), evacuate to a vacuum degree of 0.08MPa, then fill in nitrogen with a nitrogen flow rate of 4L / min, add 3.6g of metallic sodium powder crushed in liquid nitrogen, mix the hard carbon powder and metallic sodium powder evenly, heat to 190℃ for pre-sodium reaction, and the pre-sodium reaction time is 1.5h to obtain pre-sodium hard carbon.
[0058] 10 g of pre-sodiumized hard carbon and 25 g of dimethyl terephthalate were mixed uniformly at 55° C. and reacted at 165° C. for 1.5 h to obtain pre-sodiumized hard carbon coated with dimethyl terephthalate.
[0059] Example 2
[0060] 60g of phosphorylated reed powder (phosphorylated reed powder is obtained by mixing reed powder and phosphoric acid at a mass ratio of 10:0.8 for 1.5h, and the mass concentration of phosphoric acid is 60%) and 36g of waste bisphenol A phenolic resin powder are mixed and crushed into blocks, pre-carbonized at 550°C for 2.5h, and the pre-carbonized product is crushed to obtain a hard carbon precursor. 40g of hard carbon precursor, 28g of waste bisphenol A phenolic resin powder, 9g of nano titanium oxide, and 9g of nano tin oxide are mixed, and the temperature is increased to 1450°C at a rate of 7°C / min, and carbonized at 1450°C for 1.5h and then crushed to obtain hard carbon powder.
[0061] Put 30g of hard carbon powder into a vacuum vibration dryer (power is 5kW), evacuate to a vacuum degree of 0.09MPa, then fill in argon gas with an argon flow rate of 7L / min, add 8g of metallic sodium powder crushed in liquid nitrogen, mix the hard carbon powder and metallic sodium powder evenly, heat to 210℃ for pre-sodium reaction, and the pre-sodium reaction time is 0.75h to obtain pre-sodium hard carbon.
[0062] 10 g of pre-sodiumized hard carbon and 35 g of dimethyl terephthalate were mixed uniformly at 65° C. and reacted at 175° C. for 1 h to obtain pre-sodiumized hard carbon coated with dimethyl terephthalate.
[0063] Example 3
[0064] 60g of phosphorylated bamboo powder (phosphorylated bamboo powder is obtained by mixing bamboo powder and phosphoric acid at a mass ratio of 10:0.7 for 2.5 hours, and the mass concentration of phosphoric acid is 58%) and 30g of waste polyethylene terephthalate plastic powder are mixed and crushed into blocks, pre-carbonized at 500°C for 3 hours, and the pre-carbonized product is crushed to obtain a hard carbon precursor. 40g of hard carbon precursor, 25g of waste polyethylene terephthalate plastic powder and 15g of nano-alumina are mixed, heated to 1400°C at a rate of 5°C / min, carbonized at 1400°C for 2 hours, and then crushed to obtain hard carbon powder.
[0065] Put 30g of hard carbon powder into a vacuum vibration dryer (power is 5kW), evacuate to a vacuum degree of 0.085MPa, then fill in nitrogen with a nitrogen flow rate of 5L / min, add 6g of metallic sodium powder crushed in liquid nitrogen, mix the hard carbon powder and metallic sodium powder evenly, heat to 200℃ for pre-sodium reaction, the pre-sodium reaction time is 1h, and obtain pre-sodium hard carbon.
[0066] 10 g of pre-sodiumized hard carbon and 30 g of dimethyl terephthalate were mixed uniformly at 60° C. and reacted at 170° C. for 1.5 h to obtain pre-sodiumized hard carbon coated with dimethyl terephthalate.
[0067] Comparative Example 1
[0068] The pre-carbonization step and nano-alumina of Example 3 were omitted, the amount of metallic sodium powder was changed to 12 g, and the other conditions were the same as those of Example 3.
[0069] Comparative Example 2
[0070] The phosphorylated bamboo powder in Example 3 was omitted, the carbonization temperature in Example 3 was changed to 1800° C., the heating rate in the carbonization process was changed to 15° C. / min, and the other conditions were the same as in Example 3.
[0071] The coated pre-sodiumized hard carbon prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are used to prepare pre-sodiumized hard carbon dry-process electrodes, respectively. 20g of the pre-sodiumized hard carbon coated with dimethyl terephthalate of Examples 1 to 3 and Comparative Examples 1 to 2, 2g of polyethylene terephthalate and 1.5g of conductive carbon black are respectively mixed evenly. The obtained mixture is dry-coated on a carbon-coated aluminum foil with a thickness of 30μm (the carbon layer thickness is 4μm) with a coating thickness of 70μm. The mixture is hot-pressed on a double-roller machine with a titanium nitride protective layer (the gap of the double-roller machine is 30μm, the pressure is 40 tons, and the molding temperature is 110°C) to obtain the pre-sodiumized hard carbon dry-process electrode.
[0072] The negative electrode sheet (sodium sheet), the positive electrode sheet (pre-sodiumized hard carbon dry-process sheet), 30μL electrolyte and polyethylene diaphragm were assembled into a button cell. The electrolyte was NaPF6 / diethanol dimethyl ether (concentration was 1.5mol / L). In an argon-filled glove box, the electrochemical performance test was carried out on a new Wei mihw-200-160ch battery tester. The charge and discharge voltage range was 0.01 to 2.0V. At the same time, the rate performance (2C / 0.1C) and cycle performance (0.2C / 0.2C, 300 cycles) of the button cell were tested.
[0073] The specific capacity of the first cycle of hard carbon deintercalation of sodium in Example 1 is 682 mAh·g -1 The specific capacity of the first hard carbon embedded with sodium is 660 mAh g -1The first coulombic efficiency is 96.8%, the rate performance (2C / 0.1C) is 91.8%, and the capacity retention rate after 300 cycles is 92%.
[0074] The specific capacity of the first cycle of hard carbon deintercalation of sodium in Example 2 is 756 mAh·g -1 The specific capacity of the first hard carbon embedded with sodium is 722 mAh g -1 The first coulombic efficiency is 95.5%, the rate performance (2C / 0.1C) is 92.5%, and the capacity retention rate after 300 cycles is 92.8%.
[0075] The specific capacity of the first cycle of hard carbon deintercalation of sodium in Example 3 is 810 mAh·g -1 The specific capacity of the first hard carbon embedded with sodium is 781 mAh g -1 The first coulombic efficiency is 96.4%, the rate performance (2C / 0.1C) is 93.1%, and the capacity retention rate after 300 cycles is 93.0%.
[0076] The specific capacity of the first cycle of hard carbon deintercalation of sodium in comparative example 1 is 550 mAh g -1 The specific capacity of the first hard carbon embedded with sodium is 530 mAh g -1 The first coulombic efficiency is 96.3%, the rate performance (2C / 0.1C) is 78.1%, and the capacity retention rate after 300 cycles is 79.5%.
[0077] The specific capacity of the first cycle of hard carbon deintercalation of sodium in comparative example 2 is 544 mAh g -1 The specific capacity of the first hard carbon embedded with sodium is 514 mAh g -1 The first coulombic efficiency is 94.5%, the rate performance (2C / 0.1C) is 80.2%, and the capacity retention rate after 300 cycles is 77.3%.
[0078] The method of the present invention is simple, easy to implement and not prone to produce by-products. The pre-sodiumization of the present invention successfully inhibits the irreversible decomposition of the electrolyte and other side reactions during the first cycle. Sodium terephthalate and dimethyl terephthalate form an electronically insulating, ionically conductive and insoluble SEI film on the pre-sodiumized hard carbon dry-process electrode, which works in conjunction with the SEI film generated by the battery cycle to protect the negative electrode of the sodium ion battery and improve the various performances of the sodium ion battery. The pre-sodiumized hard carbon of the present invention can simultaneously improve the initial charge and discharge efficiency, cycle performance and rate performance of the negative electrode of the sodium ion battery, has a high sodium storage capacity and good safety performance.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing pre-sodiumized hard carbon coated with a coating agent, characterized in that: The following steps are included: 1) Pre-carbonizing the phosphorylated biomass and waste plastic powder to obtain a hard carbon precursor; 2) carbonizing the hard carbon precursor, waste plastic powder and nano oxide to obtain hard carbon powder; 3) Pre-sodiumizing hard carbon powder and metallic sodium powder under an inert gas to obtain pre-sodiumized hard carbon; 4) mixing the pre-sodium-treated hard carbon and the coating agent and reacting them to obtain the pre-sodium-treated hard carbon coated with the coating agent; The phosphorylated biomass is obtained by mixing biomass powder and phosphoric acid in a mass ratio of 10:0.5-1; the biomass powder comprises one or more of bagasse, bamboo powder and reed powder; Step 2) the nano-oxide comprises one or more of nano-aluminum oxide, nano-silicon oxide, nano-titanium oxide, nano-magnesium oxide, nano-tin oxide and nano-silicon oxide; Step 4) The coating agent is dimethyl terephthalate.
2. The preparation method according to claim 1, characterized in that: Step 1) The mass ratio of the phosphorylated biomass to the waste plastic powder is 3:1-2.
3. The preparation method according to claim 1 or 2, characterized in that: The waste plastic powder in step 1) and step 2) comprises one or more of waste polyethylene terephthalate, waste phenolic resin and waste polycarbonate.
4. The preparation method according to claim 3, characterized in that: Step 1) The temperature of the pre-carbonization reaction is 200-600°C, and the time of the pre-carbonization reaction is 2-5 hours; Step 2) The carbonization temperature is 1300-1500°C, the carbonization time is 1-3h, and the rate of heating to the carbonization temperature is 2-7°C / min.
5. The preparation method according to claim 4, characterized in that: In step 2), the mass ratio of the hard carbon precursor, waste plastic powder and nano oxide is 4:2-3:1-2; in step 3), the mass ratio of the hard carbon powder and metallic sodium powder is 10:1-3.
6. The preparation method according to claim 4 or 5, characterized in that: Step 3) The temperature of the pre-sodiumization reaction is 180-220° C., and the time of the pre-sodiumization reaction is 0.5-1.5 h; the metallic sodium powder is metallic sodium powder crushed in liquid nitrogen; the inert gas is nitrogen or argon, and the flow rate of the inert gas is 2-8 L / min.
7. The preparation method according to claim 6, characterized in that: The mass ratio of pre-sodiumized hard carbon to dimethyl terephthalate is 1:2-4; the mixing temperature is 55-65°C, the reaction temperature is 160-180°C, and the reaction time is 0.5-2h.
8. Pre-sodiumized hard carbon coated with a coating agent prepared by the preparation method according to any one of claims 1 to 7.
9. The method for preparing pre-sodiumized hard carbon dry-process electrode sheet by using pre-sodiumized hard carbon coated with a coating agent as claimed in claim 8, characterized in that: The following steps are included: The pre-sodiumized hard carbon coated with a coating agent, a binder and conductive carbon black are mixed, and the mixture is hot-pressed and coated on a carbon-coated aluminum foil to obtain a pre-sodiumized hard carbon dry-process electrode; The thickness of the carbon-coated aluminum foil is 25-35 μm, and the coating thickness of the mixture on the carbon-coated aluminum foil is 60-75 μm; The mass ratio of the pre-sodiumized hard carbon coated by the coating agent, the binder and the conductive carbon black is 20:1-3:1-2; the binder is polyvinylidene fluoride and / or polyethylene terephthalate.
10. The pre-sodiumized hard carbon dry-process electrode prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Hard carbon material for power and energy-storage battery and preparation method thereof
CN101916845A
Phosphorus-nitrogen-doped biomass hard carbon material as well as preparation method and application thereof
CN113745509A